Prevalence and Genotype Distribution of High-Risk Human Papillomavirus Infection Among Sub-Saharan African Women: A Systematic Review and Meta-Analysis - Seyoum, Ayichew; Assefa, Nega; Gure, Tadesse; Seyoum, Berhanu; Mulu, Andargachew; Mihret, Adane (Frontiers in Public Health, 2022)
Among sub-Saharan African women, cervical cancer is steadily increasing with more than 75,000 new cases and 50,000 deaths annually. Due to the vast ethno-geography variation, Africa harbors heterogeneous genotypes of HPV. High-risk HPV genotypes such as hr HPV-16, -18,-35, and -52 are abundantly reported in sub-Saharan Africa. The purpose of this systematic review and meta-analysis is to generate evidence on the prevalence and the genotype distribution of hr HPV among sub-Saharan African countries. We conducted a systematic review by following the preferred reporting items for systematic reviews and Meta-analysis and used PubMed and Google Scholar databases to identify published studies between 2001 and 2021. We included studies that used PCR-based or hybrid testing to assess the presence of HPV DNA in a cervical biopsy, cervical swelling, and vaginal swelling. The comprehensive meta-analysis software using a random-effects model was used to determine the pooled prevalence and type-specific distribution of HPV with 95% confidence intervals. The I-squared statistic was used to describe the amount of heterogeneity. This review included 27 studies conducted in 19 sub-Saharan countries. A total of 16,506 women were included in a systematic review and 5,303 of them were infected with the hr HPV infection. Out the hr HPV infected women, only 3,075 women results were eligible for meta-analysis. The prevalence of hr HPV infection among women with different health conditions ranges from 10.7 to 97.2% while the pooled prevalence of hr HPV in sub-Saharan African countries is 32.3 % (95%CI: 26.6 –38.7). Among 3,075 women, 424 (13.8%), 305 (9.9%) and 279 (9%) were infected with HPV-16, HPV-52 and HPV-18, respectively. HPV-16 and HPV-52 are the main genotypes causing the hr HPV infection in the Eastern Africa and Southern African sub-contents, whereas HPV-16 and HPV-35 are the main genotypes in the Western African countries. Depending on a number of factors, especially women’s health conditions, the high rate of HPV with inconsistent hr HPV distribution shows that HPV infection is a growing public health challenge in sub-Saharan African countries. Therefore, it is important to take associated factors into account in order to implement a vaccination-based prevention strategy and be effective.